FERTILIZAÇÃO FOLIAR DE SORGO COM MANIPUEIRA (EXTRATO LÃQUIDO DAS RAÃZES DE MANDIOCA) - Ponte, J. Júlio da; Aragão, M. L.; Silveira Filho, J.; Andrade, N. C. (REVISTA DE AGRICULTURA, 2015)
FERTILIZAÇÃO FOLIAR DE SORGO COM MANIPUEIRA (EXTRATO LÃQUIDO DAS RAÃZES DE MANDIOCA)